English as a Medium of Instruction in non-English Subject; Exploring the Students Language Proficiency - Asshofiah, Khodijah; Tarwiyah, Siti; Dewi, Nuna Mustikawati (Allure Journal, 2025)
In facing the current era of globalization, it is necessary to implement an application that supports students to improve their English proficiency. The research problems are how is the implementation of EMI in non English subject and how is the students’ class language proficiency situation during joining the EMI-based class? The writers used the descriptive qualitative case study method. The subject of the research were students at Maahad Tahfiz Al-Qur'an Darul Falah Selangor, Malaysia. The instruments were field observation, interviews, questionnaires. The research findings and discussion are highlight the dual role of EMI in improving English language proficiency while facilitating content mastery, despite challenges such as code-switching and students' varying levels of self-confidence. EMI improved language skills; its effectiveness depends on strategies tailored to support students' diverse needs. The conclusion are EMI improved language skills; its effectiveness depends on strategies tailored to support students' diverse needs. These insights contribute to optimizing EMI practices and advancing education policies that align with global academic demands. The integration of language and subject knowledge through EMI  prepares students for academic success and equips them with the linguistic and cognitive skills. The recommendation are further researchin the other scope of EMI is needed to explore the long-term impact of EMI on students' academic performance and language proficiency, particularly in diverse educational contexts to serve as a valuable tool for promoting inclusive and  effective educational     environment.